Understanding the Intensive Care Unit Experience of Patients and Relatives at the End-of-Life During the Coronavirus Disease 2019 Pandemic. (July 2022) - Eskell, Matthew; Thompson, Jamie; Powell, Ohema; Torlinski, Tomasz; Mullhi, Randeep
The coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on patients and relatives' experiences of end-of-life care, as well as changing the provision of these services in intensive care units (ICUs) across the world. Established methods for assisting relatives through the grieving process have required modification due to the unique features and circumstances surrounding deaths from this disease. This mixed-methods study from the United Kingdom (UK) aims to review data from patients who died in a large ICU (the unit had a capacity for more than 100 ventilated patients), over the course of approximately 1 year. The inpatient noting of these patients was reviewed specifically for details of visiting practices, chaplaincy support, and patient positioning (prone vs supine) prior to death. Using this data, recommendations are made to improve end-of-life care services. To allow relatives the opportunity to attend the ICU, there is a need for early recognition of patients approaching the end of life. Clear explanations of the need for prone positioning and increased access to chaplaincy services were also identified.